Receiver-Triggered Handshake Protocol for DTN in Disaster Area - Ryoma Yamashita; Kazumasa Takami (Future Internet, 2015)
When a disaster hits a wide area, communication services for public use will be rendered unavailable. This will make it difficult to confirm the safety of people in the disaster area. A solution to this problem is to form delay/disruption tolerant networks (DTN) using mobile terminals of victims, those of rescuers, who serve as information carriers, and terminals (servers) in shelters. In this paper, we propose using a receiver-triggered handshake protocol for communication between these terminals. We have developed the bundle layer protocol for this handshake method. The proposed method has been implemented on a network simulator to build an evaluation environment. The disaster area has been modeled on an area around Shinjuku Station in Tokyo. Victims are randomly distributed in the area. We have compared the proposed method with Epidemic Routing and Spray and Wait in terms of the delivery rate at which messages reach their destinations, and the length of time taken for messages to reach their destinations. We have found that the delivery rate of the three methods are, more or less, the same, but that the proposed method is superior to the other two methods in terms of storage usage and battery consumption of terminals, and the number of bundles generated in the network.